Infective Endocarditis Following Selective Angioembolisation for Lower Gastrointestinal Tract Bleeding: A Case Report - Michelle Bai; Ferdinand Ong; Daniel Kozman (European Medical Journal Gastroenterology)
Selective angioembolisation is a common treatment modality for lower gastrointestinal bleeding. Sepsis is an uncommon complication of the procedure, and infective endocarditis is even rarer yet. Presented here is a case of a male in his 50s who received selective angioembolisation to a branch of the right colic artery to control lower gastrointestinal bleeding. He subsequently developed sepsis and acute cardiac failure due to Enterococcus faecalis bacteraemia and infective endocarditis, requiring a valve replacement surgery and an extended course of antibiotics.